What is Your Degree Worth? The Relationship Between Post–Secondary Programs and Employment Outcomes - Fenesi, Barbara; Sana, Faria (Canadian Journal of Higher Education, 2015)
There is a long-standing debate over the value of certain postsecondary programs in facilitating employment after graduation. The National Graduate Survey (2005) was used to examine how graduates of various programs differ in their pursuits of higher education, employment status, job-program relatedness and job qualifications. Results suggest that graduates from humanities are more likely to pursue higher education, are less likely to be employed full time, are more likely to have jobs unrelated to their program, and are more likely to be overqualified for their jobs. These findings highlight that humanities programs may not provide the knowledge and skills that are in current economic demand.